When Music Mattered: American Music in the Sixties - Wierzbicki, James Eugene (Cham (CH) Palgrave Macmillan, 2022)
This book examines the American Sixties, and how that period’s socio-political essence was reflected and refracted in certain forms of the period’s music. Its five main chapters bear the names of familiar musical categories: ’Folk,’ ‘Rock,’ ‘Jazz,’ ‘Avant-Garde,’ ‘Classical.’ But the book’s real subject matter—treated at length in the Prologue and the Epilogue but spread throughout all that comes between—is the Sixties’ tangled mess of hopes and frustrations, of hungers as much for self-identity as for self-indulgence, of crises of conscience that bothered Americans of almost all ages and regardless of political persuasion.
James Wierzbicki (1948) lives in the Australian town of Coober Pedy. For twenty years, he was the classical music critic for the St. Louis Post-Dispatch and other American newspapers, and for another twenty years a professor at the University of California-Irvine, the University of Michigan, and the University of Sydney.
Keywords: 20th Century (1901-2000); Music history; Cuckoo; Folk music; Popular music; Jazz; Avant-garde; USA